PENGARUH KETAATAN AUDITOR, PENGALAMAN AUDIT, GENDER DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGEMENT - Risqullah Diffa Miraza (2020)
The purpose of this study was to determine the effect of auditor compliance, audit experience, gender and task complexity on audit judgment in the South Jakarta KAP. This study takes a sample of external auditors who are in KAP South Jakarta who have worked for at least one year as respondents. The sampling technique uses a purposive random sampling method. The sample in this study were 50 respondents from 22 public accounting firms in South Jakarta. Testing the hypothesis of this study using Multiple Linear Regression Analysis using the Statistical Program and Service Solution (SPSS) version 25 and a significance level of 5%. The results of the study partially showed that the auditor's compliance and task complexity variables had a significant effect on audit judgment and the audit experience and gender variables had no significant effect on audit judgment.